2018
DOI: 10.4309/jgi.2018.38.13
|View full text |Cite
|
Sign up to set email alerts
|

Perfectionism Predicts Disordered Gambling Via Financially Focused Self-Concept

Abstract: Perfectionism has been implicated in several psychiatric disorders, including eating disorders, anxiety disorders, and depression. In the current research, we extended the analysis of perfectionism to understand disordered gambling. Unlike other life domains in which people with perfectionistic tendencies can objectively control outcomes (e.g., dieting to control one's body shape or weight in eating disorders), perfectionism in the gambling context is unique because there is little to no objective control over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 35 publications
2
9
0
Order By: Relevance
“…These results complement research showing that financially focused gamblers are more likely to have gambling problems, to feel financially deprived, to have low global self-esteem, and to delay-discount monetary rewards, as well as to be more materialistic, neurotic, and perfectionistic and less conscientious and extraverted (Tabri, Shead, & Wohl, 2017;Tabri, Werner, Milyavskaya, & Wohl, 2018;.…”
Section: Discussionsupporting
confidence: 82%
“…These results complement research showing that financially focused gamblers are more likely to have gambling problems, to feel financially deprived, to have low global self-esteem, and to delay-discount monetary rewards, as well as to be more materialistic, neurotic, and perfectionistic and less conscientious and extraverted (Tabri, Shead, & Wohl, 2017;Tabri, Werner, Milyavskaya, & Wohl, 2018;.…”
Section: Discussionsupporting
confidence: 82%
“…Unfortunately, gambling for financial gain is a well-established predictor of disordered gambling (e.g., Clarke et al, 2006;Hahn, Wilson, McRae, & Gilbert, 2013;Lister, Nower, & Wohl, 2016;MacLaren, Ellery, & Knoll, 2015;Tabri et al, 2015). Players who are high in financial focus are therefore at heightened risk for disordered gambling compared to players low in financial focus (Tabri et al, 2019;Tabri, Salmon, et al, in press;Tabri, Shead et al, 2017;Tabri, Werner et al, 2018;.…”
Section: Financial Focus and Disordered Gamblingmentioning
confidence: 99%
“…Another reason for the association between a financially focused self-concept and disordered gambling is because those who are more financially focused tend to have etiological risk factors of gambling disorder compared to those who are less financially focused (Tabri, Salmon et al, in press;Tabri, Werner et al, 2018;. For example, among players without gambling problems, showed that having a financial focus was moderately and positively associated with etiological risk factors for disordered gambling, including erroneous gambling beliefs, financial dissatisfaction, low perceived selfefficacy to cope with life adversity, and impulsivity.…”
Section: Financial Focus and Disordered Gamblingmentioning
confidence: 99%
“…Such maladaptive perfectionism has been linked to many negative outcomes, one of which is addictive behavior. Previous research has identified the predictive effect of maladaptive perfectionism on various forms of addictive behaviors, such as alcohol problems [ 17 ], disordered gambling [ 18 ], exercise addiction [ 19 ], and work addiction [ 20 ].…”
Section: Introductionmentioning
confidence: 99%